BIMBINGAN KONSELING PADA SISWA YANG BERPERILAKU MENYIMPANG AKIBAT PERCERAIAN ORANG TUA DI SEKOLAH KASIH KARUNIA JAKARTA - Frieska Putrima Tadung (POIMEN Jurnal Pastoral Konseling, 2021)
One of the reasons behind this research is that at the Kasih Karunia School, deviant behavior is a serious problem. This went on for so long that it caused problems for the teacher and his friends. This deviant behavior can be categorized as behavioral and ethical problems or social deviations that are not in accordance with the norms and customs in society. Some of these deviant behaviors occur because of the factors that influence students, namely, the condition of divorced parents which causes a lack of affection and attention from each parent for their child, causing the child to become emotional at one time, especially when his parents decided to divorce. This is the background for conducting an in-depth study with the aim of the meaning of counseling guidance on students who behave deviantly due to the divorce of their parents at Kasih Karunia School in Jakarta. The approach in this research is to use qualitative methods. The object of the research is special Christian students at Kasih Karunia School Jakarta.